Youth organizations and their role in the world politics - A. V. Vovenda (Vestnik MGIMO-Universiteta)
This paper introduces the characteristics of youth organizations as contemporary actors of the world politics, identified their key features and specific activities, the main issues and conflicts which are involved in their operation processes, and the key perspectives of their development. The paper analyzed the specifics of cooperation between youth organizations and other actors of the world politics, and also the influence of the political and financial elites on the youth policy in general. Also considered the largest and the most dynamic recent youth organizations